ROUGHNESS OF PROCESSING POWER FUNCTION FOR CUTTING ALLOY STEEL BY ELECTROSIS EROSION - Alin NIOAŢĂ (Fiabilitate şi Durabilitate)
Ruggedness represents the imprints/traces left on the work surface after the processing and it consists of deviation of the 3rd degre and deviation of the 4th degre. They are microunevenness, which depend on the cinematic of the processing and have a temporal character, consisting of striations or scratches and snatches. In this paper in order to establish the mathematical pattern of the dependence of processing ruggedness on the induced power within the workspace Ra=f(P) polynomial functions of the 1st, 2nd and 3rd degrees and exponential functions were used.